Solar Cycle-Modulated Deformation of the Earth–Ionosphere Cavity - Bozóki, Tamás; Sátori, Gabriella; Williams, Earle; Mironova, Irina; Steinbach, Péter; Bland, Emma C.; Koloskov, Alexander; Yampolski, Yuri M.; Budanov, Oleg V.; Neska, Mariusz; Sinha, Ashwini K.; Rawat, Rahul; et al. (Frontiers in Earth Science, 2021)
The Earth–ionosphere cavity resonator is occupied primarily by the electromagnetic radiation of lightning below 100 Hz. The phenomenon is known as Schumann resonances (SR). SR intensity is an excellent indicator of lightning activity and its distribution on global scales. However, long-term measurements from high latitude SR stations revealed a pronounced in-phase solar cycle modulation of SR intensity seemingly contradicting optical observations of lightning from satellite, which do not show any significant solar cycle variation in the intensity and spatial distribution of lightning activity on the global scale. The solar cycle-modulated local deformation of the Earth–ionosphere cavity by the ionization of energetic electron precipitation (EEP) has been suggested as a possible phenomenon that may account for the observed long-term modulation of SR intensity. Precipitating electrons in the energy range of 1-300 keV can affect the Earth–ionosphere cavity resonator in the altitude range of about 70-110 km and modify the SR intensities. However, until now there was no direct evidence documented in the literature supporting this suggestion. In this paper we present long-term SR intensity records from eight stations, each equipped with a pair of induction coil magnetometers: five high latitude (|lat|>60o), two mid-high latitude (50o<|lat|<60o) and one low latitude (|lat|< 30o). These long-term, ground-based SR intensity records are compared on the annual and interannual timescales with the fluxes of precipitating 30-300 keV medium energy electrons provided by the POES NOAA-15 satellite and on the daily timescale with electron precipitation events identified using a SuperDARN radar in Antarctica. The long-term variation of the Earth–ionosphere waveguide’s effective height as inferred from its cutoff frequency is independently analyzed based on spectra recorded by the DEMETER satellite. It is shown that to account for all our observations one needs to consider both the effect of solar X-rays and EEP which modify the quality factor of the cavity and deform it dominantly over low- and high latitudes, respectively. Our results suggest that SR measurements should be considered as an alternative tool for collecting information about and thus monitoring changes in the ionization state of the lower ionosphere associated with EEP.